2020
DOI: 10.4155/bio-2020-0168
|View full text |Cite
|
Sign up to set email alerts
|

Intact mAb LC–MS for Drug Concentration from Pre-Clinical Studies: Bioanalytical Method Performance and in-Life Samples

Abstract: Background: Antibody biotherapeutic measurement from pharmacokinetic studies has not been traditionally based on intact molecular mass as is the case for small molecules. However, recent advancements in protein capture and mass spectrometer technology have enabled intact mass detection and quantitation for dosed biotherapeutics. A bioanalytical method validation is part of the regulatory requirement for sample analysis to determine drug concentration from in-life study samples. Results/methodology: Here, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…On the other hand, if the internal standard binds to the same epitope on the capture reagent as the analyte (e.g., stable isotope labeled IS or mAb analogue with same sequence at binding region), it theoretically can compensate for binding saturation and provide extended linear curve range. , Other considerations for IS use include potential ionization suppression or complicated mass spectra due to coeluting IS, which may be a reason for limited use of IS for intact protein assay. Indeed, recent works have demonstrated that the intact protein LC/MS assays do not necessarily require internal standards. , Currently, there exists insufficient data to determine the optimal IS workflow for intact protein LC/MS assays, but advancement in method development will likely enable a recommendation eventually.…”
Section: Points To Considermentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, if the internal standard binds to the same epitope on the capture reagent as the analyte (e.g., stable isotope labeled IS or mAb analogue with same sequence at binding region), it theoretically can compensate for binding saturation and provide extended linear curve range. , Other considerations for IS use include potential ionization suppression or complicated mass spectra due to coeluting IS, which may be a reason for limited use of IS for intact protein assay. Indeed, recent works have demonstrated that the intact protein LC/MS assays do not necessarily require internal standards. , Currently, there exists insufficient data to determine the optimal IS workflow for intact protein LC/MS assays, but advancement in method development will likely enable a recommendation eventually.…”
Section: Points To Considermentioning
confidence: 99%
“…Carrier proteins or internal standard may also be used in the elution step and can impact stability of processed samples. In general, intact protein samples processed and analyzed by LC/MS have demonstrated 24–36 h of postextract stability in 1–5% acetic acid at 4 °C, and 5 cycles of freeze–thaw may be acceptable for serum samples containing mAb therapeutics. , The type of well seal (e.g., slit, foil, others) may also impact stability and protein oxidation. For all the sample preparation steps, it is recommended to use sample tubes that have been designed to minimize nonspecific protein binding to prevent analyte loss.…”
Section: Points To Considermentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof-of-concept and to better understand the advantages of the ZenoTOF 7600 system, the intact mAb and subunit mAb quantitation performed herein were compared with existing instruments and publications to establish parity. , Here, reference standard material was spiked into serum at various levels to establish linearity in assay and instrument response over the range of 2–50 μg/mL in serum. Example MS1 data used for absolute quantitation of the intact GSKmAb is shown in Figure and Figure SI-4.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, LC-MS analysis of a biotherapeutic mAb extracted from serum is presented, and intact mass detection, mass quantitation, and subunit characterization experiments are demonstrated. Recently, a number of laboratories have shown absolute quantitation of mAbs and other protein therapeutics from plasma or serum. In these cases, intact mass measurement was sufficient, but detailed characterization information (such as PTM localization) was not obtained. Here, top-down characterization data from a dosed biotherapeutic is presented as a proof-of-principle measurement for a potential application across pharmacokinetics (PK) or biotransformation studies.…”
Section: Introductionmentioning
confidence: 99%